Human Resources Planning of Government Apparatus in Special Region of Yogyakarta in 2017 - Rahayu, Riska; Atmojo, Muhammad Eko (Government Studies of Muhammadiyah Malang University/AIPPTM, 2019)
Human resources planning apparatus is a system of development of human resource management. With the existence of good planning in managing the human resources of an agency, the expectation is to achieve the goals of the organization/institution with various planned strategies. The Regional Staffing Agency (BKD) of Daerah Istimewa Yogyakarta (DIY) collaborates between national policies and regional policies, especially in staffing affairs if there is a connection with the DIY Specialties business as one of the strategies in addressing the problems between the two. In this study used a qualitative descriptive method. Collection through interviews and data analysis in the form of documents. In this study, the authors explain about the human resource planning apparatus carried out by the Regional Government of DIY in 2017. The result of this research is that The Regional Staffing Agency of DIY in fulfilling needs, especially in staffing affairs has been well prepared and with a fairly fast process. When an organization requires new employees to complete the government organization, BKD DIY will respond and of course with consideration of employees who are good enough from the aspect of ability and qualifications of employees who are in accordance with the organization or agency need.Keywords: Human Resources Planning, Human Resources Management, Staffing Agency.